Silicon-carbon composite material, preparation method thereof, pole piece, application and electrochemical device
By using a silicon-carbon composite material formed by reacting metal compound aerosol with nano-silicon porous carbon in lithium-ion batteries, and undergoing plasma-enhanced gas-phase carbon coating, the problems of poor rate performance and high expansion rate of existing materials are solved, and efficient electrochemical performance and simple preparation process are achieved.
Patent Information
- Application Number
- CN202411725360.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-15
AI Technical Summary
The existing silicon-carbon composite materials have poor rate performance and high expansion rate in lithium-ion batteries, and the production method is complex and not conducive to commercialization.
The reaction is carried out using a first silicon carbon material including a metal compound aerosol and a porous carbon filled with nanosilicon to form a second silicon carbon material, and a gas-phase carbon coating is enhanced by plasma to form a cladding layer with a metal compound layer and/or a metal elemental layer.
The rate performance of silicon-carbon composite materials in lithium-ion batteries is improved, the expansion rate of the electrode sheet is reduced, the preparation method is simplified, and it is suitable for industrial production.
Smart Images

Figure CN119833589A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon composite material and a preparation method, a pole piece, an application and an electrochemical device thereof. Background Art
[0002] With the rapid development of science and technology, advanced devices such as drones, electric vehicles, and smart wearable devices have higher requirements for the lightweight and endurance of lithium-ion batteries. However, commercial graphite negative electrode materials are gradually approaching their theoretical capacity, and it is increasingly difficult to improve the energy density of lithium-ion batteries. Therefore, it is necessary to develop new high-capacity lithium-ion battery negative electrode materials. At present, the new type of nano-silicon-carbon material is a promising lithium-ion battery negative electrode material because of its high theoretical capacity, high initial efficiency, long cycle, and abundant raw materials.
[0003] At present, the production of new nano silicon carbon usually uses porous carbon skeleton materials as the substrate to carry out chemical vapor deposition of gaseous silicon source. This method can evenly deposit small-sized nano amorphous silicon in the pores of activated carbon, and preferably the carbon source gas is chemically deposited at a lower temperature to reduce the surface activity of nano silicon and fill the excess pores. However, the traditional low-temperature chemical vapor deposition coating is time-consuming and has a low conversion rate, which greatly affects the production efficiency and the generated carbon layer has a large number of defects, resulting in poor conductivity and insufficient mechanical strength of the carbon layer. Therefore, the current rate performance of silicon carbon materials is poor, and the carbon layer may break after multiple cycles, causing rapid capacity decay. Therefore, designing a more reasonable coating layer is the focus of research in this technical field. Chinese patent application CN117712359A proposes to increase the mechanical strength of the coating layer by coating a metal oxide coating on the outside of the carbon layer through a liquid phase method and heat treatment. However, this does not solve the problem that the carbon layer deposition rate is slow and the conductivity is poor, resulting in poor battery capacity performance, first coulombic efficiency, cycle stability and rate performance of the resulting silicon-carbon negative electrode material assembly. In addition, the preparation steps are cumbersome and not conducive to commercialization. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects of the prior art that the battery assembled with silicon-carbon composite materials has poor rate performance and a high expansion rate of the pole piece during charging and discharging, and provide a silicon-carbon composite material and its preparation method, pole piece, application and electrochemical device. The battery assembled with the silicon-carbon composite material of the present invention has better rate performance, and the expansion rate of the pole piece during charging and discharging is low. The preparation method of the silicon-carbon composite material of the present invention is simple and easy to operate, can realize continuous processing, and is conducive to industrial production.
[0005] The present invention adopts the following technical solutions to solve the above technical problems.
[0006] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps:
[0007] S1, reacting an aerosol including a metal compound with a first silicon-carbon material to obtain a second silicon-carbon material; the first silicon-carbon material includes porous carbon filled with nano-silicon;
[0008] S2. Performing plasma-enhanced gas-phase carbon coating on the second silicon-carbon material.
[0009] In the present invention, the mass content of silicon in the first silicon-carbon material may be 20%-70%, preferably 50%-60%, for example 52%.
[0010] In the present invention, the specific surface area of the first silicon-carbon material may be 50-500m 2 / g, preferably 200-300m 2 / g, for example 221m 2 / g.
[0011] In the present invention, the preparation method of the first silicon-carbon material can be conventional in the art, and preferably comprises the following steps: subjecting porous carbon and a gaseous silicon source to a silicon deposition reaction.
[0012] The type of the porous carbon may be conventional in the art, preferably one or more of activated carbon, carbon molecular sieve, capacitor carbon and template carbon, such as activated carbon.
[0013] The specific surface area of the porous carbon is preferably 500-2000 m 2 / g, for example 1800m 2 / g. The pore volume of the porous carbon may be >0.3 cm 3 / g, for example 1.2cm 3 / g. The D50 of the porous carbon may be 5-10 μm, for example, 8 μm. The D10 of the porous carbon may be ≥2 μm, for example, 3 μm. The D90 of the porous carbon may be ≤18 μm, for example, 18 μm. The Dmax of the porous carbon may be ≤25 μm, for example, 25 μm.
[0014] The type of the gaseous silicon source may be one or more of monosilane, disilane and silane derivatives, such as monosilane.
[0015] The mass volume ratio of the porous carbon and the gaseous silicon source may be 1 kg: (1000-1400) L, for example, 1 kg: 1200L.
[0016] The silicon deposition reaction is preferably carried out under a protective gas, wherein the protective gas is preferably one or more of nitrogen, argon and helium, such as argon.
[0017] The equipment for the silicon deposition reaction can be conventional in the art, preferably a rotary kiln or a fluidized bed, preferably a fluidized bed with an atomizing device on the top.
[0018] The temperature of the silicon deposition reaction may be 400-700°C, for example 500°C.
[0019] The silicon deposition reaction time may be 2-12 hours, for example 10 hours.
[0020] The rate of heating from room temperature to the temperature of the silicon deposition reaction may be 1-5° C. / min, for example, 3° C. / min.
[0021] The mass molar ratio of the porous carbon to the metal compound may be 5 kg: (10-14) mol, for example 5 kg: 12 mol.
[0022] In the present invention, the aerosol of the metal compound refers to a colloidal dispersion system formed by a metal compound solution dispersed and suspended in a gas medium, also known as a gas dispersion system, with a size of 0.001-100 microns, and the dispersion medium is gas.
[0023] In the present invention, the D50 of the aerosol of the metal compound may be 0.2-10 μm, for example 0.2-3 μm.
[0024] In the present invention, the aerosol of the metal compound can be obtained by atomizing a metal compound solution.
[0025] Among them, the types of metal elements in the metal compound may include conventional metal types in the art, preferably one or more of Ag, Cu, Fe, Ni, Co, Mn, Ti, Au, Sn, Ge, In, Zn, Mo, Al, Nb, W and Sb, such as Ti, Zn, Ag or Ni.
[0026] Wherein, the metal compound is preferably an organic metal compound and / or an inorganic metal compound; the organic metal compound preferably includes an organic metal salt, a metal alkoxide or a metal coordination compound; the organic metal salt preferably includes one or more of an alkoxide, a metal β-diketone chelate, an amino salt, a bismuth salt, an acetylacetonate and an acetate, such as zinc acetate; the metal alkoxide is preferably tetraisopropoxytitanium; the metal coordination compound is preferably (HFAC)Ag(SEt2); the inorganic metal compound is preferably an inorganic metal salt; the inorganic metal salt preferably includes a nitrate and / or a halide, such as nickel nitrate;
[0027] Among them, the solvent in the metal compound solution is preferably an organic solvent, more preferably one or more of acetone, acetylacetone, n-butanol, dimethylamide, dimethyl sulfoxide, ethanol, methanol, isopropanol, tetrahydrofuran, toluene, xylene, dichloroethane, chloroform, n-hexane and cyclohexane, such as toluene and / or ethanol.
[0028] Wherein, in the metal salt solution, the molar concentration of the metal salt may be 0.0001 mol / L-1 mol / L, preferably 0.01-0.2 mol / L, such as 0.1 mol / L.
[0029] The atomization method may be conventional in the art, preferably one or more of ultrasonic atomization, pneumatic atomization, mesh atomization and electrostatic atomization, such as pneumatic atomization.
[0030] The atomization rate may be 0.1-5 L / min, for example 2 L / min.
[0031] The pressure during atomization may be 1-10 MPa, for example 3 MPa.
[0032] In S1 of the present invention, the reaction is preferably carried out in a fluidized bed with an atomizing device. Preferably, the metal salt solution is atomized into an aerosol and introduced into the atomizing device of the fluidized bed under the transport of an inert atmosphere. The type of the inert atmosphere can be conventional in the art, such as nitrogen. The flow rate of the inert atmosphere can be 1-100 L / min, for example 10 L / min.
[0033] In S1 of the present invention, the reaction temperature may be 100-700°C, such as 300, 400 or 500°C.
[0034] In S1 of the present invention, the reaction time may be 0.1-5 h, such as 0.5, 2 or 4 h.
[0035] In S1 of the present invention, during the reaction, the pressure of the system may be 10-1000000 Pa, for example, 101325 Pa.
[0036] In S1 of the present invention, the equipment for the reaction may be conventional in the art, preferably a rotary kiln or a fluidized bed, preferably a fluidized bed with an atomizing device on the top.
[0037] In S2 of the present invention, in the plasma-enhanced gas-phase carbon coating, the plasma is preferably formed by one or more of dielectric barrier discharge, jet discharge, glow discharge and corona discharge, such as dielectric barrier discharge. When the plasma-enhanced gas-phase carbon coating is performed, the pressure of the plasma may be 10-100000 Pa, such as 101325 Pa or 2660 Pa.
[0038] In S2 of the present invention, the carbon source used in the plasma enhanced gas phase carbon coating can be a gas phase hydrocarbon mixture, preferably one or more of methane, ethane, propane, isopropane, butane, isobutane, ethylene, propylene, acetylene, butene and natural gas, such as acetylene, methane or ethylene.
[0039] In S2 of the present invention, the plasma enhanced gas phase carbon coating preferably further comprises a carrier gas. The type of the carrier gas may be one or more of hydrogen, argon, ammonia, phosphine, boron, hydrogen sulfide, hydrogen selenide and hydrogen telluride, such as argon and / or hydrogen.
[0040] In S2 of the present invention, during the plasma enhanced gas phase carbon coating, the volume concentration of the carbon source may be 10%-90%, for example 16.7%, 22.2% or 50%. The volume concentration represents the percentage of the volume of the carbon source to the total gas volume during the plasma enhanced gas phase carbon coating.
[0041] In S2 of the present invention, the temperature of the plasma enhanced gas phase carbon coating may be 400-700°C, for example 600°C.
[0042] In S2 of the present invention, the rate of increasing the temperature from the reaction temperature of step S1 to the temperature of the plasma enhanced gas phase carbon coating may be 1-5°C / min, for example 3°C / min.
[0043] In S2 of the present invention, the time of the plasma enhanced gas phase carbon coating may be 2-24 hours, for example 6 hours.
[0044] In a preferred embodiment, in step S2, during the plasma enhanced gas phase carbon coating, the carbon source is acetylene, the carrier gas is argon, and the volume concentration of the carbon source is 50%.
[0045] In a preferred embodiment, in step S2, during the plasma enhanced gas phase carbon coating, the carbon source is methane, the carrier gas is hydrogen and argon, and the volume concentration of the carbon source is 22.2%.
[0046] In a preferred embodiment, in step S2, during the plasma enhanced gas phase carbon coating, the carbon source is ethylene, the carrier gas is hydrogen and argon, and the volume concentration of the carbon source is 22.2%.
[0047] In the present invention, the steps S1 and S2 are preferably carried out in the same device, for example, in a fluidized bed with an atomizing device on the top.
[0048] The present invention also provides a silicon-carbon composite material, which is prepared by the preparation method of the silicon-carbon composite material as described above.
[0049] The present application also provides a silicon-carbon composite material, which includes a second silicon-carbon material and a carbon coating layer coated on the surface of the second silicon-carbon material;
[0050] The second silicon-carbon material includes a first silicon-carbon material and a first coating layer coated on the surface of the first silicon-carbon material, wherein the first coating layer includes a metal compound layer and / or a metal single substance layer; and carbon material is distributed in the first coating layer;
[0051] The first silicon-carbon material includes porous carbon filled with nano-silicon.
[0052] In the present invention, the type of porous carbon in the first silicon-carbon material can be conventional in the art, preferably one or more of activated carbon, carbon molecular sieve, capacitor carbon and template carbon, such as activated carbon.
[0053] In the present invention, the specific surface area of the porous carbon in the first silicon-carbon material is preferably 500-2000m 2 / g, for example 1800m 2 / g. The pore volume of the porous carbon in the first silicon-carbon material may be greater than 0.3 cm 3 / g, for example 1.2cm 3 / g. The D50 of the porous carbon in the first silicon-carbon material may be 5-10 μm, for example, 8 μm. The D10 of the porous carbon in the first silicon-carbon material may be ≥2 μm, for example, 3 μm. The D90 of the porous carbon in the first silicon-carbon material may be ≤18 μm, for example, 18 μm. The Dmax of the porous carbon in the first silicon-carbon material may be ≤25 μm, for example, 25 μm.
[0054] In the present invention, the mass content of silicon in the first silicon-carbon material may be 20%-70%, preferably 50%-60%, for example 52%.
[0055] In the present invention, the specific surface area of the first silicon-carbon material may be 50-500m 2 / g, preferably 200-300m 2 / g, for example 221m 2 / g.
[0056] In the present invention, the type of metal in the metal compound layer and / or the metal single substance layer in the first coating layer can be achieved by changing the type of metal salt.
[0057] In the present invention, the types of metal elements in the first coating layer may include conventional metal types in the art, preferably one or more of Ag, Cu, Fe, Ni, Co, Mn, Ti, Au, Sn, Ge, In, Zn, Mo, Al, Nb, W and Sb, such as Ti, Zn, Ag or Ni.
[0058] In the present invention, the metal compound layer is preferably a metal oxide layer or a metal nitride layer. The metal oxide layer is preferably a titanium dioxide layer and / or a nickel oxide layer. The metal single substance layer is preferably a silver single substance layer and / or a nickel single substance layer.
[0059] In the present invention, the thickness of the first coating layer may be 10-300 nm, for example, 30 nm.
[0060] In the present invention, the mass content of carbon in the first coating layer may be less than 5wt%, for example, 1.1wt%. The mass content of carbon refers to the percentage of the mass of carbon in the first coating layer to the mass of the second silicon-carbon material.
[0061] In the present invention, the mass content of the metal in the first coating layer may be less than 5wt%, such as 0.4wt%. The mass content of the metal represents the percentage of the mass of the metal in the first coating layer to the mass of the second silicon-carbon material.
[0062] In the present invention, the mass of carbon in the carbon coating layer in the silicon-carbon composite material may be less than 5wt%, for example, 2wt%. The mass content of carbon represents the percentage of the mass of carbon in the carbon coating layer to the mass of the silicon-carbon composite material.
[0063] In the present invention, the morphology and composition of the carbon coating layer can vary according to the types of carbon source and carrier gas during carbon coating. The carbon coating layer is preferably layered, granular, sheet-like, nanotube-like or nanowire-like, such as layered, sheet-like or nanotube-like.
[0064] In the present invention, the specific surface area of the silicon-carbon composite material can be 3-15m 2 / g, such as 3.31, 4.62, 4.66 or 10.73m 2 / g.
[0065] The present invention also provides a pole piece, which comprises the silicon-carbon composite material as described above.
[0066] In the present invention, preferably, the electrode sheet is a negative electrode sheet.
[0067] The present invention also provides an application of the pole piece as described above in an electrochemical device.
[0068] The present invention also provides an electrochemical device, which comprises the pole piece as described above.
[0069] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0070] The reagents and raw materials used in the present invention are commercially available.
[0071] The positive and progressive effects of the present invention are:
[0072] (1) The silicon-carbon composite material of the present invention comprises, in sequence, a second silicon-carbon material and a carbon coating layer coated on the surface of the second silicon-carbon material; the second silicon-carbon material comprises a first silicon-carbon material and a first coating layer coated on the surface of the first silicon-carbon material, the first coating layer comprising a metal compound layer and / or a metal single substance layer; a carbon material is distributed in the first coating layer; the first silicon-carbon material comprises porous carbon filled with nano-silicon. The porous carbon skeleton in the first silicon-carbon material provides a buffer space and a conductive structure for the nano-silicon; the carbon material in the first coating layer is uniformly distributed between the metal compound layer and / or the metal single substance layer, which can prevent the metal compound and / or the metal single substance from agglomerating during the growth process and can enhance the conductivity; the external carbon coating layer can reduce the specific surface area and surface activity of the silicon-carbon composite material and increase the conductivity of the silicon-carbon composite material, thereby improving its electrochemical performance.
[0073] (2) The battery assembled from the silicon-carbon composite material of the present invention has better rate performance, and the expansion rate of the pole piece during the charge and discharge process is low. The preparation method of the silicon-carbon composite material of the present invention is simple and easy to operate, can realize continuous processing, and is conducive to industrial production.
[0074] (3) The preparation method of the silicon-carbon composite material of the present invention is simple and easy to operate, can realize continuous processing, and is conducive to industrial production. Preferably, the present invention can also change the type of metal compound and the process parameters of carbon coating according to application requirements to achieve the purpose of customized growth of carbon coating layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 This is a microscopic image of the first silicon-carbon material in Example 1.
[0076] Figure 2 This is the adsorption-desorption isotherm of the first silicon-carbon material in Example 1.
[0077] Figure 3 This is a microscopic image of the second silicon-carbon material in Example 1.
[0078] Figure 4 This is the XRD diagram of the second silicon-carbon material in Example 1.
[0079] Figure 5 This is a microscopic image of the silicon-carbon composite material obtained in Example 4.
[0080] Figure 6 This is a microscopic image of a single particle of the second silicon-carbon material in Example 1.
[0081] Figure 7 This is a microscopic image of a single particle of the second silicon-carbon material in Comparative Example 2. DETAILED DESCRIPTION
[0082] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0083] Example 1
[0084] S1: (1) 10 kg of activated carbon material (specific surface area 1800 m 2 / g, pore volume is 1.2cm 3 / g, D50 is 8μm, D10 is 3μm, D90 is 18μm, and Dmax is 25μm) is placed in a fluidized bed with an atomizer on the top, argon gas is introduced to exhaust the air, so that the system is in an inert gas atmosphere, the temperature is increased from room temperature to 500°C at a heating rate of 3°C / min, 20L / min of monosilane is introduced, and a nano-silicon deposition process is carried out for 10 hours to obtain the first silicon-carbon material.
[0085] (2) Tetraisopropoxytitanium was dissolved in toluene to form a 0.1 mol / L solution. An aerosol with a particle size D50 of 0.2-3 μm was generated from 240 L of the solution using a pneumatic atomizer. The atomization rate was 2 L / min and the pressure was 3 MPa. The aerosol was introduced into the fluidized bed from the atomization device at the top under the transport of nitrogen. The nitrogen flow rate was 10 L / min. The temperature of the fluidized bed system was maintained at 500 °C and operated at normal pressure (101325 Pa). When the aerosol came into contact with the high-temperature dust formed by the first silicon-carbon material, decomposition and heterogeneous chemical reactions occurred. After 2 hours of reaction, a layer of nano-TiO2 / carbon coating was formed on the surface of the first silicon-carbon material to obtain a second silicon-carbon material.
[0086] S2: Continue to increase the temperature of the fluidized bed from 500°C to 600°C at a heating rate of 3°C / min, introduce 5L / min of acetylene and 5L / min of argon, form plasma at 1 standard atmospheric pressure through a DBD-PECVD device (dielectric barrier discharge plasma enhanced chemical vapor deposition device) and enter the fluidized bed, react for 6 hours to achieve the outer layer of layered carbon coating. By comparing the carbon content of the material before and after coating, it can be obtained that the carbon content in the layered carbon coating layer is 2wt%.
[0087] The microscopic image of the first silicon carbon material Figure 1 shown. Figure 1 Part a is the SEM image of the first silicon-carbon material. Figure 1 Part b of FIG. 1 is the EDS image of the first silicon-carbon material. Figure 1 From part a, we can see that nano-silicon is evenly distributed in the porous carbon particles, and there is no free silicon overflowing from the outside of the particles.
[0088] The first silicon-carbon material is heated to 1200°C at a heating rate of 1°C / min in an air atmosphere. The first silicon-carbon material is completely burned into CO2 in an air atmosphere, and the remaining Si in the material is completely oxidized into SiO2. The mass of the remaining SiO2 is converted into the mass of Si by molecular weight conversion, and then divided by the total weight of the first silicon-carbon material to obtain the Si content. It is calculated that the mass content of silicon in the first silicon-carbon material is 52%. The specific surface area of the first silicon-carbon material is 221m 2 / g. The adsorption-desorption isotherm of the first silicon-carbon material is as follows Figure 2 As shown. Figure 2 It can be seen that the material exhibits a typical type I curve, indicating that silicon is deposited in the activated carbon material and a large number of micropores remain.
[0089] The microscopic image of the second silicon carbon material is as follows Figure 3 shown. Figure 3 Part a is the SEM image of the second silicon-carbon material. Figure 3 Part b of FIG. 1 is the EDS image of the second silicon-carbon material. Figure 3 From the part b, we can see that the Ti element is evenly distributed without obvious aggregation or impoverishment. It can be seen that TiO2 is evenly distributed on the surface of the first silicon-carbon material. The diffraction pattern of the second silicon-carbon material at the diffraction angle 2θ of 10-90° XRD was tested using BRUKER D8 ADVANCE ECO. The XRD pattern is shown in Figure 4 As shown by Figure 4 It can be seen that the metal compound in the material is calibrated as anatase TiO2. The XRF elemental analysis test using BRUKER S2 PUMA Series shows that the Ti content of the nano-TiO2 / carbon coating layer in the second silicon-carbon material is 0.4wt%. In the second silicon-carbon material, the thickness of the nano-TiO2 / carbon coating layer is 30nm. The carbon content in the nano-TiO2 / carbon coating layer in the second silicon-carbon material was tested using a LECO CS844 carbon-sulfur analyzer. By comparing the carbon content of the materials before and after coating, it can be found that the carbon content of the nano-TiO2 / carbon coating layer is 1.1wt%.
[0090] Example 2
[0091] The only difference from Example 1 is that the tetraisopropoxytitanium in step S1 (2) is replaced by zinc acetate, and the solvent is replaced by ethanol from toluene; the second silicon-carbon material obtained is a nano zinc oxide / carbon coating layer formed on the surface of the first silicon-carbon material.
[0092] Example 3
[0093] The only difference from Example 1 is that the tetraisopropoxytitanium in step S1 (2) is replaced by (HAFC)Ag(SEt2) (silver hexafluoroacetylacetonate diethyl sulfide complex); the reaction temperature in step S1 (2) is 300°C, the reaction time is 4 hours, and the second silicon-carbon material obtained is a silver element / carbon coating layer formed on the surface of the first silicon-carbon material; the gas in step S2 is replaced by 2L / min methane, 5L / min argon and 2L / min hydrogen, and the DBD-PECVD process is carried out under a vacuum degree of 20Torr (2660Pa) to obtain a graphene sheet.
[0094] Example 4
[0095] The only difference from Example 1 is that the tetraisopropoxytitanium in step S1 (2) is replaced by nickel acetate, the solvent is replaced by ethanol from toluene, the reaction time in step S1 (2) is 0.5 h, and the second silicon-carbon material obtained is a nano-nickel oxide / carbon coating layer formed on the surface of the first silicon-carbon material; the gas in step S2 is replaced by 2 L / min ethylene, 5 L / min argon and 2 L / min hydrogen, and the nano-nickel oxide / carbon coating layer formed in step S1 is reduced to a nickel element / carbon coating layer in this step.
[0096] Figure 5 This is a microscopic image of the silicon-carbon composite material obtained in Example 4. Figure 5 It can be seen that a carbon layer similar to carbon nanotubes grows on the surface of the silicon-carbon composite material.
[0097] Comparative Example 1
[0098] The only difference from Embodiment 1 is that step S1 (2) is omitted.
[0099] Comparative Example 2
[0100] The only difference from Example 1 is that the pneumatic atomizer in step S1 (2) is replaced with a pneumatic spray device to generate droplets with a particle size D50 of 100-500 μm from the solution.
[0101] Comparative Example 3
[0102] S1: (1) 10 kg of activated carbon material (specific surface area 1800 m 2 / g, pore volume is 1.2cm 3 / g, D50 is 8μm, D10 is 3μm, D90 is 18μm, and Dmax is 25μm) is placed in a fluidized bed with an atomizer on the top, argon gas is introduced to exhaust the air, so that the system is in an inert gas atmosphere, the temperature is increased from room temperature to 500°C at a heating rate of 3°C / min, 20L / min of monosilane is introduced, and a nano-silicon deposition process is carried out for 10 hours to obtain the first silicon-carbon material.
[0103] (2) The temperature of the fluidized bed was further increased from 500°C to 600°C at a heating rate of 3°C / min, and 5 L / min of acetylene and 5 L / min of argon were introduced. A plasma was formed at 1 standard atmospheric pressure through a DBD-PECVD device and then entered the fluidized bed. The reaction lasted for 6 hours to achieve the outer layer of layered carbon coating.
[0104] S2: After the fluidized bed is cooled to 500°C, tetraisopropoxytitanium is dissolved in toluene to form a 0.1 mol / L solution. An aerosol with a particle size D50 of 0.2-3 μm is generated from 240 L of solution using a pneumatic atomizer. The atomization rate is 1 L / min and the pressure is 3 MPa. The aerosol is introduced into the fluidized bed from the atomization device at the top under the transport of nitrogen. The nitrogen flow rate is 10 L / min. The fluidized bed system temperature is maintained at 500°C and operated at normal pressure. When the aerosol contacts the high-temperature dust formed in step S1, decomposition and heterogeneous chemical reactions occur. After 2 hours of reaction, a layer of nano-TiO2 / carbon coating is formed on the surface of the material formed in step S1.
[0105] Effect Example 1
[0106] The structure of the silicon-carbon composite material obtained in Examples 1-4 includes a second silicon-carbon material and a carbon coating layer coated on the surface of the second silicon-carbon material; the second silicon-carbon material includes a first silicon-carbon material and a first coating layer coated on the surface of the first silicon-carbon material, the first coating layer includes a metal compound layer and / or a metal element layer; carbon material is distributed in the first coating layer; the first silicon-carbon material includes porous carbon filled with nano-silicon.
[0107] The silicon-carbon composite materials prepared in the above examples and comparative examples were tested for specific surface area and powder resistivity.
[0108] The specific surface areas of the silicon-carbon composite materials prepared in the above-mentioned embodiments and comparative examples were respectively tested using the fully automatic specific surface area and pore size analysis NOVAtouchTM produced by Quantachrome Instruments, Inc. of the United States.
[0109] The resistivity of the silicon-carbon composite materials prepared in the above-mentioned embodiment and comparative example was tested respectively by using a powder resistivity tester under the condition of 8 MPa.
[0110] The results are shown in Table 1.
[0111] Table 1
[0112]
[0113] Effect Example 2
[0114] Electrochemical performance test: The silicon-carbon composite material, conductive carbon black and polyacrylic acid prepared in the above embodiments and comparative examples were dispersed in water in a mass ratio of 7:2:1 to prepare a slurry, coated on a copper foil, dried at 70°C, rolled and cut into a pole piece with a diameter of 12 mm as the anode, a metal lithium sheet as the cathode, and a 1 mol / L LiPF6 three-component mixed solvent with a volume ratio of ethyl carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1 mixed electrolyte. The diaphragm was Celgard 2400. The 2032 button battery was assembled in a glove box filled with argon.
[0115] Electrical performance testing is carried out on the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.
[0116] The test conditions for the first reversible capacity and first coulombic efficiency of the battery are: at room temperature, charge and discharge at a constant current of 0.1C, and the charge and discharge voltage is limited to 0.005-1.5V.
[0117] The rate performance test is carried out under the same test conditions. First, two cycles of 0.1C constant current charge and discharge are carried out, and then 5 cycles are carried out at 0.2C, 0.5C, 1C, 2C, and 5C discharge rates respectively to obtain the capacity of the corresponding rate.
[0118] The 1.5-cycle full-charge expansion rate is obtained by dividing the electrode thickness after 1.5 cycles by the original electrode thickness and multiplying it by 100%.
[0119] The 10-week cycle retention rate is obtained by performing 10 cycles at 0.1C and multiplying the ratio of the discharge capacity in the 10th cycle to the discharge capacity in the 1st cycle by 100%.
[0120] The test results are shown in Table 2.
[0121] Table 2
[0122]
[0123] By comparing the above embodiments and comparative examples, it can be found that compared with comparative example 1, the expansion performance and cycle performance of the silicon-carbon composite materials containing the metal compound / carbon material composite coating layer in embodiments 1-4 are significantly improved.
[0124] Comparing Example 1 with Comparative Examples 2 and 3, Example 1 achieved the best performance index. Compared with Example 1, Comparative Example 2 used a spray device instead of an atomizing device, and the droplet size generated by the spray was larger, the propagation distance was short, and the coating effect was not ideal. Using EDS equipment, the element distribution of single particles in the second silicon-carbon material prepared in Example 1 and the second silicon-carbon material prepared in Comparative Example 2 was compared, and the results were as follows: Figure 6 and Figure 7As shown. Figure 6 As shown, the Ti element introduced by the atomization device in Example 1 is evenly distributed on the particle surface, and there is no vacancy or agglomeration on the surface. Figure 7 As shown, the Ti element introduced by the atomization device in Comparative Example 2 showed significant agglomeration of small particles on the particle surface, and there were still a large number of vacancies without Ti elements on the particle surface, resulting in the failure of TiO2 to achieve a good coating effect, so the capacity was significantly reduced, and the improvement of rate, expansion rate and cycle was not as good as that of Example 1. Compared with Example 1, Comparative Example 3 used an aerosol method to coat the TiO2 oxide-carbon material in the outer layer. The TiO2 nanoparticles in the outer layer had a high specific surface area and high activity, resulting in a significant increase in the specific surface area of the sample in Comparative Example 3, and a significant decrease in the first coulomb efficiency. However, the introduction of TiO2 can improve ionic conductivity, SEI composition and mechanical strength of the material. Compared with Comparative Example 1 in which TiO2 was not introduced, the rate performance and cycle performance were improved, and the expansion rate was also reduced.
[0125] Compared with Comparative Example 1, the first reversible capacity of Examples 2 and 4 is lower. The reason may be that in Examples 2 and 4, ethanol is selected as the solvent when obtaining the metal compound / carbon material composite coating layer. During the reaction, ethanol will oxidize nano-silicon to produce SiOx with low first coulomb efficiency and capacity, and the first coulomb efficiency of the oxide itself is also lower than that of the silicon-carbon material.
[0126] Compared with Comparative Example 1, the silicon-carbon composite material in Example 1 includes a TiO2 / carbon coating layer, so it has a higher coulombic efficiency (91.6%). Furthermore, the silicon-carbon composite material in Example 1 has a denser carbon layer outside the TiO2 / carbon coating layer, so it shows a lower specific surface area of 3.31 m 2 / g. Therefore, compared with Comparative Example 1, the silicon-carbon composite material of Example 1 can ensure the integrity of the particles and reduce the occurrence of side reactions at the same rolling thickness. In addition, benefiting from the zero expansion property of TiO2 during the lithium insertion and extraction process, the silicon-carbon composite material of Example 1 presents the lowest expansion rate of 94%.
[0127] Compared with other embodiments, embodiments 3 and 4 have lower powder resistivity, because in the presence of metal compound catalysts (Ag and NiO), the growth of carbon source can be controlled to obtain carbon layers with different morphologies and high conductivity. In embodiment 3, the silver / carbon composite coating layer and the graphene layer make important contributions to the conductivity of the material, so that the silicon-carbon composite material of embodiment 3 has the lowest powder resistivity of 0.22Ω·cm, the highest 2C rate capacity of 1521.3mAh / g, and exhibits excellent cycle stability, with a capacity retention rate of up to 92.1% after 10 cycles.
[0128] In summary, different types of metal compounds can be customized and grown by aerosol chemical vapor deposition (AACVD) and exhibit different properties (such as high strength, high conductivity, high catalytic properties, etc.). These properties can be further combined with PECVD carbon coating to obtain high-quality carbon layers. The silicon-carbon material finally prepared has the advantages of low expansion, high capacity, good stability, and good rate performance.
[0129] The above is only a partial embodiment of the present invention, and any person skilled in the art may modify the technical solution described above or modify it into an equivalent technical solution. Although the present invention provides specific embodiments, it should be understood that the present invention may be further improved. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes that are out of the scope disclosed in this application and are made with conventional techniques known in the art. Without departing from the concept of the present invention, all other implementation methods that can be thought of by ordinary technicians in this field without creative work, and other simple replacements and various changes to the technical solution of the present invention, all belong to the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: S1, reacting an aerosol including a metal compound with a first silicon-carbon material to obtain a second silicon-carbon material; the first silicon-carbon material includes porous carbon filled with nano-silicon; S2. Performing plasma-enhanced gas-phase carbon coating on the second silicon-carbon material.
2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1)-(9): (1) The D50 of the aerosol of the metal compound is 0.2-10 μm, for example 0.2-3 μm; (2) The aerosol of the metal compound is obtained by atomizing a metal compound solution; Wherein, the type of metal element in the metal compound is preferably one or more of Ag, Cu, Fe, Ni, Co, Mn, Ti, Au, Sn, Ge, In, Zn, Mo, Al, Nb, W and Sb, such as Ti, Zn, Ag or Ni; Wherein, the metal compound is preferably an organic metal compound and / or an inorganic metal compound; the organic metal compound preferably includes an organic metal salt, a metal alkoxide or a metal coordination compound; the organic metal salt preferably includes one or more of an alkoxide, a metal β-diketone chelate, an amino salt, a bismuth salt, an acetylacetonate and an acetate, such as zinc acetate; the metal alkoxide is preferably tetraisopropoxytitanium; the metal coordination compound is preferably (HFAC)Ag(SEt2); the inorganic metal compound is preferably an inorganic metal salt; the inorganic metal salt preferably includes a nitrate and / or a halide, such as nickel nitrate; The solvent in the metal compound solution is preferably an organic solvent, more preferably one or more of acetone, acetylacetone, n-butanol, dimethylamide, dimethyl sulfoxide, ethanol, methanol, isopropanol, tetrahydrofuran, toluene, xylene, dichloroethane, chloroform, n-hexane and cyclohexane, such as toluene and / or ethanol; Wherein, the atomization method is preferably one or more of ultrasonic atomization, pneumatic atomization, mesh atomization and electrostatic atomization, such as pneumatic atomization; Wherein, the atomization rate is preferably 0.1-5 L / min, for example 2 L / min; Wherein, the pressure during atomization is preferably 1-10MPa, for example 3MPa; (3) In S1, the reaction temperature is 100-700°C, for example, 300, 400 or 500°C; (4) In S1, the reaction time is 0.1-5 h, for example 0.5, 2 or 4 h; (5) In S2, the carbon source used in the plasma enhanced gas phase carbon coating is a gas phase hydrocarbon mixture, preferably one or more of methane, ethane, propane, isopropane, butane, isobutane, ethylene, propylene, acetylene, butene and natural gas, such as acetylene, methane or ethylene; (6) In S2, during the plasma enhanced gas phase carbon coating, the volume concentration of the carbon source is 10%-90%, for example, 16.7%, 22.2% or 50%; the volume concentration represents the percentage of the volume of the carbon source to the total gas volume during the plasma enhanced gas phase carbon coating; (7) In S2, the temperature of the plasma enhanced gas phase carbon coating is 400-700°C, for example, 600°C; (8) In S2, the rate of increasing the temperature from the reaction temperature of step S1 to the temperature of the plasma enhanced gas phase carbon coating is 1-5°C / min, for example 3°C / min; and, (9) In S2, the time of the plasma enhanced gas phase carbon coating is 2-24 hours, for example 6 hours.
3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1)-(3): (1) The mass content of silicon in the first silicon-carbon material is 20%-70%, preferably 50%-60%, for example 52%; (2) The specific surface area of the first silicon-carbon material is 50-500m 2 / g, preferably 200-300m 2 / g, for example 221m 2 / g; and, (3) The method for preparing the first silicon-carbon material comprises the following steps: subjecting porous carbon and a gaseous silicon source to a silicon deposition reaction; The specific surface area of the porous carbon is preferably 500-2000 m 2 / g, for example 1800m 2 / g; the pore volume of the porous carbon is preferably >0.3cm 3 / g, for example 1.2cm 3 / g; the D50 of the porous carbon is preferably 5-10 μm, for example 8 μm; the D10 of the porous carbon is preferably ≥2 μm, for example 3 μm; the D90 of the porous carbon is preferably ≤18 μm, for example 18 μm; the Dmax of the porous carbon is preferably ≤25 μm, for example 25 μm; Wherein, the type of the gaseous silicon source is preferably one or more of monosilane, disilane and silane derivatives, such as monosilane; Wherein, the mass volume ratio of the porous carbon and the gaseous silicon source is preferably 1 kg: (1000-1400) L, for example 1 kg: 1200 L; Wherein, the temperature of the silicon deposition reaction is preferably 400-700°C, for example 500°C; Wherein, the silicon deposition reaction time is preferably 2-12 hours, for example 10 hours; The rate of heating from room temperature to the temperature of the silicon deposition reaction is preferably 1-5°C / min, such as 3°C / min.
4. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method of any one of claims 1 to 3.
5. A silicon-carbon composite material, characterized in that: It includes a second silicon-carbon material and a carbon coating layer coated on the surface of the second silicon-carbon material; The second silicon-carbon material includes a first silicon-carbon material and a first coating layer coated on the surface of the first silicon-carbon material, wherein the first coating layer includes a metal compound layer and / or a metal single substance layer; and carbon material is distributed in the first coating layer; The first silicon-carbon material includes porous carbon filled with nano-silicon.
6. The silicon-carbon composite material according to claim 5, characterized in that: The silicon-carbon composite material satisfies one or more of the following conditions (1)-(8): (1) The type of metal element in the first coating layer is one or more of Ag, Cu, Fe, Ni, Co, Mn, Ti, Au, Sn, Ge, In, Zn, Mo, Al, Nb, W and Sb, such as Ti, Zn, Ag or Ni; (2) The metal compound layer is a metal oxide layer or a metal nitride layer; the metal oxide layer is preferably a titanium dioxide layer and / or a nickel oxide layer; (3) The metal single substance layer is a silver single substance layer and / or a nickel single substance layer; (4) The thickness of the first coating layer is 10-300 nm, for example 30 nm; (5) The mass content of carbon in the first coating layer is less than 5 wt%, for example, 1.1 wt%; the mass content of carbon represents the percentage of the mass of carbon in the first coating layer to the mass of the second silicon-carbon material; (6) The mass content of the metal in the first coating layer is less than 5 wt%, for example, 0.4 wt%; the mass content of the metal represents the percentage of the mass of the metal in the first coating layer to the mass of the second silicon-carbon material; (7) the mass of carbon in the carbon coating layer in the silicon-carbon composite material is less than 5wt%, for example, 2wt%; the mass content of carbon represents the percentage of the mass of carbon in the carbon coating layer to the mass of the silicon-carbon composite material; and, (8) The specific surface area of the silicon-carbon composite material is 3-15 m 2 / g, such as 3.31, 4.62, 4.66 or 10.73m 2 / g.
7. The silicon-carbon composite material according to claim 5, characterized in that: The silicon-carbon composite material satisfies one or more of the following conditions (1)-(9): (1) The type of porous carbon in the first silicon-carbon material is one or more of activated carbon, carbon molecular sieve, capacitor carbon and template carbon, such as activated carbon; (2) The specific surface area of the porous carbon in the first silicon-carbon material is 500-2000 m 2 / g, for example 1800m 2 / g; (3) The pore volume of the porous carbon in the first silicon-carbon material is greater than 0.3 cm 3 / g, for example 1.2cm 3 / g; (4) The D50 of the porous carbon in the first silicon-carbon material is 5-10 μm, for example, 8 μm; (5) D10 of the porous carbon in the first silicon-carbon material is ≥2 μm, for example, 3 μm; (6) D90 of the porous carbon in the first silicon-carbon material is ≤18 μm, for example, 18 μm; (7) Dmax of the porous carbon in the first silicon-carbon material is ≤25 μm, for example, 25 μm; (8) the mass content of silicon in the first silicon-carbon material is 20%-70%, preferably 50%-60%, for example 52%; and, (9) The specific surface area of the first silicon-carbon material is 50-500m 2 / g, preferably 200-300m 2 / g, for example 221m 2 / g.
8. A pole piece, characterized in that: It comprises the silicon-carbon composite material as described in any one of claims 4 to 7.
9. Use of the electrode piece according to claim 8 in an electrochemical device.
10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 8.
Citation Information
Patent Citations
Double-shell silicon-carbon composite negative electrode material and preparation method and application thereof
CN117712359A